Osteopontin Expression in Cardiomyocytes Is Increased in Pediatric Patients With Sepsis or Pneumonia - Irion, Camila Iansen; Parrish, Kiera; John-Williams, Krista; Gultekin, Sakir H.; Shehadeh, Lina A. (Frontiers in Physiology, 2018)
Sepsis and pneumonia are major causes of death in the United States, and their pathophysiology includes infection with inflammation and immune dysfunction. Both sepsis and pneumonia cause cardiovascular dysfunction. The expression of Osteopontin (OPN) in cardiomyocytes of patients with sepsis or pneumonia, and its role the induced cardiac dysfunction have not been thoroughly investigated. OPN is a matricellular protein synthesized by multiple diseased tissues and cells including cardiomyocytes. Here we studied the expression of OPN protein using immunofluorescence in human myocardial autopsy tissues from pediatric and mid age or elderly patients with sepsis and/or pneumonia. Fourteen human myocardial tissues from six pediatric patients and eight mid-age or elderly patients were studied. Immunofluorescence was used to investigate the expression of OPN in paraffin-embedded heart sections co-stained with the myocyte markers Actin Alpha 1 (ACTA1) and Myosin Light Chain 2 (MLC2). A quantitative analysis was performed to determine the number of ACTA1 and MLC2 positive cardiomyocytes that express OPN. The results showed that OPN expression was significantly increased in cardiomyocytes in the hearts from pediatric patients with sepsis and/or pneumonia (N=3) relative to pediatric patients without sepsis/pneumonia (N=3), or adult to elderly patients with sepsis/pneumonia (N=5).. Among the older septic hearts, higher levels of cardiomyocyte OPN expression was seen only in conjunction with severe coronary arterial occlusion. This is the first study to document increased OPN expression in cardiomyocytes of pediatric subjects with sepsis or pneumonia. Our findings highlight a potentially important role for OPN in sepsis- or pneumonia-mediated cardiac dysfunction in pediatric patients.